Contradictory Mobilities and Cultural Projects of Afropolitanism African Immigrant Nurses in Vancouver, Canada - Maureen Kihika, (Anthropologica, 2024)
I explore the relationship between social class and race, through an examination of how Black nurses enact Afropolitan cultural practices to negotiate contradictory class mobilities in Vancouver. While this paper reflexively draws from my family’s lived experiences to begin thinking through the nuances of Afropolitanism, I hone the discussion in contextual reference to the class-making practices of African-born nurses. The nurses channel Afropolitan class-making projects, through which they develop a flexibility and openness of mind that enables them to reject taking on the role of victim in their contradictory mobilities. Afropolitanism refers to “an expansive politics of inclusion that seeks to position actors as part of a transnational community of Africans of the world” (Adjepong 2021, 1), to “imbue Africanness with value” (137). Merging the literature on anti-Black racism in nursing with scholarship examining relationships between social class, race, and culture, this paper draws out the promises and pitfalls of Afropolitanism through an exploration of how African immigrant nurses—part of a growing Black Canadian middle class—grapple with contradictory mobility in Canada’s racialized terrain. It contributes to discussions of the Black middle class, in the context of a “relative newness of Black middle classes” (Rollock et al. 2012, 253).